Assessment of technological development factors of the industry of the Republic of Kazakhstan - Alimbayev, A.A.; Filyuk, G.M.; Kenesheva, G.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the Message of the President N.A. Nazarbayev to the People of Kazakhstan it is said that «we have begun the Third modernization of the country. Its main task is to form a new model of economic growth that will ensure global competitiveness of Kazakhstan. Therefore, the model of economic growth of the republic, being an important element, cannot but include a strategy for technological development. It is important to focus on support of exporters in the manufacturing sector, and for this it is necessary to create and implement high-end technologies and competitive products in the sectors of the «economy of the future» by strengthening the interaction of science and business that will allow Kazakhstan to create the foundations of a post-industrial economy. Features of the development process of advanced manufacturing technologies and the technical and economic level largely determine the possibilities for the further development of the country, the ability of the industry to restructure itself and respond adequately to changing business conditions, investment and consumer demand. The decisive factor in the functioning of the economy is diversification of production, restructuring and deep and radical modernization of technological base on the basis of the convention of new industrialization. Implementation of this task is, firstly, related to a radical change in the technological basis in traditional sectors of the national economy, which can become a major factor, taking into account trends in development of the world economy. Secondly, it will give impetus to improvement of innovation system and formation of a foundation for the latest scientific and technical breakthroughs and the creation of fundamentally new sectors of the economy.
Қазақстан Республикасы өнеркəсібінің технологиялық даму факторларын бағалау
Оценка факторов технологического развития промышленности Республики Казахстан
Keywords: industry; scientific and technical progress; technological development; modernization; fixed assets; innovation; economic growth; competitiveness; digital technology; labour productivity